2018
DOI: 10.1093/sleep/zsy122
|View full text |Cite|
|
Sign up to set email alerts
|

Association between long-term exposure to air pollution and sleep disorder in Chinese children: the Seven Northeastern Cities study

Abstract: Our findings suggest that exposure to air pollutants increases the odds of sleep disorder in children and point to the need to make reducing exposure to air pollutants a public health priority.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(35 citation statements)
references
References 36 publications
0
34
0
1
Order By: Relevance
“…Our findings are also consistent with previous research [23,26,28,38], which found that increasing levels of ozone and PM 10 were associated with a reduction in sleep efficiency [23], an increase in sleep–disordered breathing (SDB) [23,26,28], and an increase in the severity of sleep apnea [38]. In a recent study across seven northeastern Chinese cities, higher long-term exposure to PM 2.5 , PM 10 , SO 2 , NO 2, and O 3 was associated with a 1.02–1.53 greater odds ratio (OR) of sleep disorders in Chinese children [39]. Moreover, a separate study reported that prenatal PM 2.5 exposure was associated with altered sleep in preschool-aged children in Mexico City [40].…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are also consistent with previous research [23,26,28,38], which found that increasing levels of ozone and PM 10 were associated with a reduction in sleep efficiency [23], an increase in sleep–disordered breathing (SDB) [23,26,28], and an increase in the severity of sleep apnea [38]. In a recent study across seven northeastern Chinese cities, higher long-term exposure to PM 2.5 , PM 10 , SO 2 , NO 2, and O 3 was associated with a 1.02–1.53 greater odds ratio (OR) of sleep disorders in Chinese children [39]. Moreover, a separate study reported that prenatal PM 2.5 exposure was associated with altered sleep in preschool-aged children in Mexico City [40].…”
Section: Discussionmentioning
confidence: 99%
“…Another study conducted in Boston revealed long-term exposure to black carbon was significantly associated with shorter sleep time among male participants and those have low socioeconomic status (Fang et al, 2015). A study conducted in seven northeastern Chinese cities presented long-term exposure to PM 2.5 increased the risk of sleep disorder among children [OR and 95%CI: 1.47 (1.34, 1.62)] (Lawrence et al, 2018). Similar to previous studies, our study found exposure to air pollution had adverse effect on sleep quality.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, a multicenter cohort study conducted in the U.S. reported exposure to PM 10 (particulate matter with aerodynamic diameters ≤10 μm) was significantly associated with decreased sleep efficiency (Zanobetti et al, 2010). A cross-sectional study conducted in northeastern China stated long-term exposures to ambient particulate matter (PM) and gaseous pollutants increased the risk of sleep disorder among children (Lawrence et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…First, while we use the whole dataset for studying the heterogeneity of OSA patients, examining more specific patient cohorts may help to reveal more interesting information, e.g., patients with Oxygen therapy or patients with hypertension and nocturia [12]. Second, other environmental factors such as air pollutions is known to be related to OSA, especially for children [24]. Studying how the disease evolve over time wrt.…”
Section: Discussionmentioning
confidence: 99%